GROWTH OF ODFL IN LESOTHO: INCREASING EDUCATIONAL ACCESS FOR MARGINALISED COMMUNITIES - Nyabanyaba, Thabiso (South African Journal of Higher Education, 2016)
This paper presents findings of a study on the capacity of open, distance and flexible learning (ODFL) in Lesotho. With an aim of increased and more strategic deployment of distance learning within and across the SADC (Southern African Development Community) region, the study undertook an evaluation of the growth of ODFL provision in Lesotho with a view to assessing its potential for increasing access to education for many marginalised members of communities. Through a documentary review of the programmes on offer and a survey of perceptions regarding ODFL programmes in Lesotho, the study revealed the potentials for this mode of delivery in providing a second chance for the many marginalised youth in the country to improve their socio-economic standing. A number of challenges for the current ODFL provisioning were also highlighted. These included lack of investment in human and material resources for ODFL in Lesotho.